PENGELOLAAN KELAS SEBAGAI UPAYA DALAM MENINGKATKAN AKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM dan BUDI PEKERTI (PAI-BP) - aji, dede (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2023)
Classroom management strategy is a pattern / strategy, which describes the steps used by teachers in creating and maintaining classroom conditions to remain conducive, so that students can learn optimally, actively, and fun effectively and efficiently to achieve learning objectives. This study, using a qualitative approach, descriptive approach, namely research aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually or in groups. Data collection methods used observation, interviews, documentation, and questionnaires. While data analysis techniques use qualitative descriptive analysis supported by percentage techniques. The results showed that classroom management strategies in PAI learning to improve student learning achievement at SDN Karikil Mangkubumi Tasikmalaya City The factors that support classroom management strategies in PAI learning to improve student learning achievement at SDN Karikil Mangkubumi Tasikmalaya City are the implementation of school rules. School vision, mission, and learning objectives based on devotion and akhlaq. Interactive learning strategies. Musholla as a place of worship and learning. The worship habituation program. Students' desire to have knowledge of Islam. While the inhibiting factors are: lack of parental support for improving the quality of children's religion. Lack of space and learning media in practicing PAI material. Students' enthusiasm, responsiveness to learning, concentration, and activeness in learning PAI are less than optimal. students do not have PAI allowance books. Lack of student confidence during PAI learning.